A escrita da língua portuguesa, como segunda língua, por surdos - Marcon, Andréia Mendiola (2013)
This study consists in an exploratory and descriptive empirical research conducted through quanti-qualitative approach, including an analysis on the writing of the Portuguese language as L2 from Libras (Brazilian Sign Laguage), L1, by six deaf professors of the Association of Parents and Friends of the Deaf (Apas). The general goal was to describe and analyze the learning process of L2 by the deaf, observing when and how they build this learning. Therefore, some specific objectives were proposed: to carry a historic-chronological study about Sign Language; to perform a theoretical trajectory about the different perspectives and theories of the acquisition of first and second language; to add considerations on Sign Language to the linguistic studies so to show its importance as L1 in accessing L2, aiming for the inclusion of the deaf in the written linguistic universe. The study focused on the generative theory perspective, seeking to answer the question: how does the deaf acquire Sign Language and, from that, use it to acquire a second language, in this specific case, Portuguese? The research is justified for helping to extend the studies on language acquisition by the deaf, more specifically on the learning of Portuguese by these subjects, which may generate further knowledge about how they express themselves through L2, in other words, how they organize their thoughts using the structure of a second language. The participants were approached in two meetings organized by Apas. Two instruments were used for data collection. The first one was a questionnaire including 12 open and semi-open questions about the acquisition of Libras and the learning of Portuguese by the deaf. The second one was the textual production of the participants, in order to verify how deaf people express themselves in the writing of Portuguese. For the analysis, the deaf participants were classified as subject 1, subject 2, subject 3, subject 4, subject 5 and subject 6. The results of this study indicate the deaf as non-competent subjects regarding the written performance of Portuguese as L2, which shows the need of a new way of thinking the teaching of this language to deaf people